2018
DOI: 10.1007/jhep09(2018)087
|View full text |Cite
|
Sign up to set email alerts
|

Neutron star mergers chirp about vacuum energy

Abstract: Observations of gravitational waves from neutron star mergers open up novel directions for exploring fundamental physics: they offer the first access to the structure of objects with a non-negligible contribution from vacuum energy to their total mass. The presence of such vacuum energy in the inner cores of neutron stars occurs in new QCD phases at large densities, with the vacuum energy appearing in the equation of state for a new phase. This in turn leads to a change in the internal structure of neutron sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…after all phase transitions have occurred. As noted in [], this leads to a modification for the equation of state in neutron stars, which could potentially be observed in gravitational waves emitted from binary merger events. It would be interesting to seek out other astrophysical phenomena sensitive to this feature of our model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…after all phase transitions have occurred. As noted in [], this leads to a modification for the equation of state in neutron stars, which could potentially be observed in gravitational waves emitted from binary merger events. It would be interesting to seek out other astrophysical phenomena sensitive to this feature of our model.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have fixed the overall zero temperature constants appearing in the free energy of all phase transitions, we also expect that in regions of the Universe which are still at high temperature, the local vacuum energy density and thus the local value of the cosmological constant to be higher. This will occur, for example, in the interior of neutron stars, and it was proposed in references [179][180][181] that the effects of this could be detected via gravitational waves generated by a binary merger event.…”
Section: 20)mentioning
confidence: 99%
“…The critical difference between the vacuum transition and the condensed matter system are finite density effects. As shown in [17] and [18], new phases can exist in a very localized region inside compact objects, or a semi-local region (confined bubbles) if the landscape contains close by, degenerate or near degenerate vacua. These confined bubbles will be the main topic of this paper.…”
Section: Introductionmentioning
confidence: 96%
“…However, under well defined assumptions, in particular that kaon condensation [26] takes place somewhat above n 0 , we show that spontaneous CP violation in the neutral Goldstone sector is triggered, resulting in axion condensation -see [27] for a first discussion of axion condensation in the context of a tuned non-standard axion. For a range of axion masses of order of the inverse radius of the NS, the axion gets sourced, with phenomenological consequences that go from a non-standard contribution to the mass of the star (closely resembling [28,29]) or the presence of an axionic brane [30], to an O(1) enhancement of the electric field in the star's magnetosphere. Other implications of such a sourcing, e.g.…”
Section: Jhep07(2020)221mentioning
confidence: 99%
“…A NS with a core of "vacuum energy" was considered as a generic scenario in [28,29], in the context of exotic QCD phases. It was found that the energy shift inside the NS leads to a significant change in the mass-radius relation of NSs, as well as to changes of the so-called chirp mass, one of main the gravitational wave observables of compact binary mergers.…”
Section: Jhep07(2020)221mentioning
confidence: 99%